Antimicrobial and antibiofilm activity of the benzoquinone oncocalyxone A. (December 2020) - da Silva, Raí Emanuel; Ribeiro, Fábio de Oliveira Silva; de Carvalho, Andressa Maria A.; Daboit, Tatiane Caroline; Marinho-Filho, José Delano Barreto; Matos, Taynara Simão; Pessoa, Otília Deusdênia Loiola; de Souza de Almeida Leite, José Roberto; de Araújo, Alyne Rodrigues; dos Santos Soares, Maria José
Abstract: Resistance to antimicrobials is a challenging issue that complicates the treatment of infections caused by bacteria and fungi, thus requiring new therapeutic options. Oncocalyxone A, a benzoquinone obtained from Auxemma oncocalyx (Allem) Taub has several biological effects; however, there is no data on its antimicrobial action. In this study, its antimicrobial and antibiofilm activities were evaluated against bacteria and fungi of clinical interest. Strains of Gram-positive and Gram-negative bacteria, and filamentous fungi and yeasts were selected to determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of oncocalyxone A. The antibacterial effect of oncocalyxone A was studied using survival curves, atomic force microscopy (AFM), and the involvement of oxidative stress. We examined the inhibitory action of the molecule on biofilm formation and its hemolytic activity against human erythrocytes. Our results showed that among the strains tested, Staphylococcus epidermidis was highly sensitive to the action of oncocalyxone A, with an MIC of 9.43 μg/mL. In most bacterial strains analyzed, a bacteriostatic effect was observed, though the molecule showed no antifungal activity. Antibiofilm activity was observed against the methicillin-resistant S. aureus bacteria. Additionally, results from atomic force microscopy imaging showed that oncocalyxone A significantly altered bacterial morphology. Further, oncocalyxone A showed no hemolytic activity at concentrations ≥151 μg/mL. Together, our results demonstrate the antibacterial and antibiofilm potential of oncocalyxone A, indicating its therapeutic potential against bacterial resistance. Graphical abstract: Image 1 Highlights: Antibacterial activity of oncocalixone A against sensitive and resistant bacteria. Study of antibacterial activity by AFM technique. Study of the participation of oxidative stress in antibacterial activity. Antibiofilm activity of oncocalixone A.